Membrane composition of jetted lipid vesicles: A Raman spectroscopy study - Kirchner, Silke R. (2012)
Microfluidic jetting is a promising method to produce giant unilamellar phospholipid vesicles for mimicking living cells in biomedical studies. We have investigated the chemical composition of membranes of vesicles prepared using this approach by means of Raman scattering spectroscopy. The membranes of all jetted vesicles are found to contain residuals of the organic solvent decane used in the preparation of the initial planar membrane. The decane inclusions are randomly distributed over the vesicle surface area and vary in thickness from a few to several tens of nanometers. Our findings point out that the membrane properties of jetted vesicles may differ considerably from those of vesicles prepared by other methods and from those of living cells.